Three Generations of Forest Peoples’ Empowerment in Indonesia: Process Towards Sustainable and Equitable Forest Management - Jun Harbi; Yukun Cao; James Thomas Erbaugh; Faris Rafi Almay Widagdo; Jerry Mauri; Supriyanto; Noril Milantara (Institut Pertanian Bogor (IPB University), 2020)
Human activities that alter land cover have destroyed natural ecosystems and caused conflict. In Indonesia, community-based forest management (CBFM) policies implemented by the government seek to empower communities, ameliorate forest conversion, and reduce environmental conflict. This article critically assesses contemporary CBFM policy in Indonesia by analyzing its history and outcomes through policy analysis. To systematically review previous literature on CBFM, this research uses the PRISMA method. It finds that communities are often able to manage forest areas sustainably through sociocultural systems that combine management customs and culture. Empowerment through CBFM policy therefore promises to promote community subsistence, equity, and security regarding forest management. However, granting total resource rights to communities can result in land conversion unless managerial safeguards are in place. Many studies find that the clarity of land boundaries, the consistency of regulation, and the partiality of land governance drive CBFM program success. To facilitate land governance for the successful implementation of Indonesian social forestry, communities need access rights, authority to manage forests, and sufficient knowledge transfer to participate in formal forest management. In contrast to previous iterations of CBFM in Indonesia, current social forestry policy acknowledges these governance needs and seeks to implement them.